THE NATIONAL ESSENCE OF GOERGIY SVIRIDOV’S “SPRING CANTATA” - Nuralieva Zukhra Anvarovna; Khusnitdinova Yulduz Madatovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the work “Spring Cantata” as part of the study of essence of the national creativity of the Russian composer of the Goergiy Vasilievich Sviridov.